ANALISIS PENGARUH KOMPETENSI, INTEGRITAS DAN INDEPENDENSI TERHADAP KUALITAS AUDIT STUDI PADA AUDITOR INSPEKTORAT KABUPATEN BENGKALIS - Agustami, Try; Azlina, Nur; Hasan, Mudrika Alamsyah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted on Auditor Office of Inspectorate of Bengkalis Regency with the aim to know the influence of variable Competence, Integrity and Independence to Quality Audit Study At Auditor Office Inspectorate Bengkalis This research uses primary data that is data obtained from interviews and giving questionnaires to all employees Auditor Office Inspectorate of Bengkalis Regency. Secondary data obtained related to the object and organizational structure of the population in this study are all employees of the Inspectorate Auditor Office of Bengkalis Regency, amounting to 13 people and sampled. The method of analysis used in this study is multiple linear regression method. From the results of tests that have been done, Partial Test (Test-t) indicates that the variable Competence, Integrity and Independence significantly influence the Quality Audit. The result of calculation of coefficient of determination (R2) is equal to 0,711 or equal to 71,1% which means, variable of Competence, Integrity and Independence together influence to Audit Quality, while the rest 22,9% influenced by other variables not examined in research this.Keyword : Competence, Integrity, Independence and Quality Audit